Kimyrsa, An Oritavancin-Containing Product: Clinical Study and Review of Properties. (23rd March 2022) - Hoover, Randall K; Krsak, Martin; Molina, Kyle C; Shah, Kairav; Redell, Mark
Abstract: Background: There is a need for improved antibiotic formulations for the treatment of acute bacterial skin and soft structure infection (ABSSSI), especially with the rise of antimicrobial resistance among Gram-positive bacteria. A new formulation of oritavancin was developed to reduce intravenous infusion volume (from 1000 mL to 250 mL), shorten infusion time (from 3 hours to 1 hour), and provide pharmacies with flexibility in oritavancin preparation (from 5% dextrose in sterile water to either normal saline or 5% dextrose in sterile water) compared with the current formulation. Methods: A total of 102 adult patients with a diagnosis of ABSSSI suspected or confirmed to be caused by a Gram-positive pathogen were randomized 1:1 to receive either the new formulation of oritavancin or the current formulation. After a single 1200-mg intravenous infusion of oritavancin, the relative area-under-the-curve exposure of the new formulation and current formulation groups were compared. Safety and tolerability of the new formulation were assessed for treatment-emergent adverse events, serious adverse events, and changes to laboratory parameters. Results: The area under the curve for 0 hour to 72 hours postdose was very similar in the new formulation group compared with the current formulation group. No differences in treatment-emergent adverse events were observed between the current and new formulation groups, and all treatment-emergent adverse events were consistent with the known safety profile of the current formulation. Conclusions: The new formulation of oritavancin with reduced volume and duration of intravenous infusion demonstrates a safety profile and pharmacokinetics similar to that of the original formulation. Abstract : A randomized, open-label, pharmacokinetics and safety study evaluated the relative exposure and safety of a new cyclodextrin-containing oritavancin formulation in subjects being treated for ABSSSI and demonstrated a favorable safety profile and similar pharmacokinetics compared with the current formulation.